Health-related quality of life in locally advanced and metastatic breast cancer: methodological and clinical issues in randomised controlled trials. Issue 7 (July 2016) - Ghislain, Irina; Zikos, Efstathios; Coens, Corneel; Quinten, Chantal; Balta, Vasiliki; Tryfonidis, Konstantinos; Piccart, Martine; Zardavas, Dimitrios; Nagele, Eva; Bjelic-Radisic, Vesna; Cardoso, Fatima; Sprangers, Mirjam A G; et al.
Summary: Breast cancer is the leading cause of cancer death among women worldwide, and increasingly, randomised controlled trials of this disease are measuring the health-related quality of life of these patients. In this systematic Review, we assess the adequacy of methods used to report health-related quality of life (HRQOL) from 49 eligible randomised controlled trials of advanced breast cancer. We compare our findings with those from the literature to investigate whether the standard of HRQOL reporting in this field has changed. We conclude that the overall reporting of HRQOL has improved, but some crucial aspects remain problematic, such as the absence of HRQOL research hypotheses and the overemphasis on statistical rather than clinical significance. Additionally, new challenges are arising with the emergence of novel treatments and the advent of personalised medicine, and improved HRQOL tools are required to cover the range of side-effects of newer therapies.